EXAMINING THE MEANING IN THE LYRICS OF THE BUAI ANAK SONG - Suhadri , Fadlika; Minawati , Rosta; Mulyadi (PT. Antis International Publisher, 2024)
Objective: This study examines the emotional and educational themes depicted in the song